Living Qur’an Dalam Studi Qur’an Di Indonesia (Kajian Atas Pemikiran Ahmad Rafiq) - HS, Muhammad Alwi; Parninsih, Iin (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2021)
Ahmad Rafiq is well-known as a Living Qur'an expert in Indonesia, in fact he is referred to as one of the main initiators. However, in the course of the study of Living Qur'an, none of Ahmad Rafiq's works became references in Living Qur'an's literature, including the Living Qur'an ontology book and Hadith from UIN Sunan Kalijaga (2007) and Ubaydi's book (2019) ). Whereas Ahmad Rafiq's Living Qur'an idea was seen in his work in 2004. Therefore, this article aims to discuss what and how Ahmad Rafiq's Living Qur'an perspective, here will also position the Living Qur'an between text studies and sociology-anthropology. Through descriptive-analytical-interpretative analysis, this article concludes that the phenomenon of Living Qur'an has existed since the era of the Prophet, this phenomenon can be found throughout the development of Muslims from time to time, both in the initial environment of the emergence of the Qur’an (Arabic) let alone outside, Indonesia for example. Ahmad Rafiq himself emphasized the reading of transmission and transformation in the study of the Living Qur'an, which contains synchronous reception values in diachronic reception form from time to time. From here, Living Qur’an is in the position of studying text and sociology-anthropology at the same time.